PERTUMBUHAN DAN PRODUKSI TANAMAN KENIKIR (Cosmos caudatus Kunth.) PADA BERBAGAI TINGKAT NAUNGAN - Revianto, Revianto; Rahayu, Arifah; Mulyaningsih, Yanyan (Universitas Djuanda Bogor, 2017)
This study was aimed at assessing the effects of shade (paranet) on the growth and production of kenikir (Cosmos caudatus). The study was conducted from April to September 2016 at the Agrotechnology Trial Farm of Djuanda University, Bogor. A split plot completely randomized design was used with shade levels, namely 0 (no shade), 25, 50, and 75% as the main plot and places of origin, namely Bogor, Cianjur, and Sukabumi as the sub plot. Results showed that 50 and 75% shades at 8 weeks after planting (WAP) significantly decreased plant height, leave length, stem diameter, harvest fresh weight and harvest dry weight. Leaf width of kenikir was found to be higher. Number of leaves of kenikir of Sukabumi and Cianjur origins was higher than that of Bogor origin. Chlorophyl content of kenikir of Cianjur origin was higher than that of Sukabumi and Bogor origins. However, biomass yield harvested from all acessions was not different. Key words: chlorophyl content, plant origin, harvest yield.